Research handbook on climate change, migration and the law - Mayer, Benoît; Crépeau, François (Research handbooks in climate law, 2017)
Concerns have arisen in recent decades about the impact of climate change on human mobility. Many people affected by climate change are forced or otherwise decide to migrate within or across international borders. Despite its clear importance, many questions remain open regarding the nature of the climate-migration nexus and its implications for laws and institutions. In the face of such uncertainty, this Research Handbook offers a comprehensive picture of laws and institutions relevant to climate migration and the multiple, often contradictory perspectives on the topic. Carefully edited chapters by leading scholars in the field provide a cross section of the various debates on what laws do, can do and should do in relation to the impacts of climate change on migration. A first part analyses the relations between climate change and migration. A second part explores how existing laws and institutions address the climate-migration nexus.-